P–806 Neogametogenesis via oocyte replication. (6th August 2021) - Petrini, A; Xie, P; Trout, A; Rosenwaks, Z; Palermo, G
Abstract: Study question: Can full preimplantation embryo development be achieved from artificial oocytes created through nuclear transfer of a haploid pseudo-blastomere (HpB) into a recipient ooplast? Summary answer: It is feasible to replicate the female genome and generate novel sibling oocytes that can yield full preimplantation embryo development, albeit at a reduced rate. What is known already: A limitation of assisted reproduction is the number of available oocytes for embryo creation. It is feasible to utilize a somatic cell nucleus to construct novel oocytes through a process known as haploidization, in which a reverse meiosis occurs after SCNT. Similarly, producing haploid parthenogenetic constructs can generate HpBs, useful for genetic testing at the pre-fertilization level or for reproduction. It is feasible to use a HpB as a nuclear donor since it has already completed homologue segregation. Study design, size, duration: This is prospective translational animal model study. Over 6 months, 556 oocytes were manipulated for the experimental group, and 158 control oocytes were employed. B6D2F1 HpBs were used to establish the procedure and acquire expertise. FVB HpBs were subsequently introduced for genetic variance. Experimental and control embryos were cultured in a time-lapse incubator (up to 96h). Cleavage parameters were compared to control. Two-sample T-tests and one-way ANOVA with Bonferroni correction were employed for statistical analysis. Participants/materials, setting, methods: A cohort of oocytes was harvested from B6D2F1 or FVB superovulated mice and artificially activated by 8% ethanol. At the 8-cell stage, HpBs were exposed to nocodazole. Another cohort of B6D2F1 oocytes was enucleated for recipient ooplasts. HpBs were individually transferred into the perivitelline space of the ooplasts alongside inactivated Sendai virus. After fusion, reconstructed oocytes with spindle development were fertilized by piezo-actuated ICSI using B6D2F1 spermatozoa. Unmanipulated and fertilized B6D2F1 oocytes served as control. Main results and the role of chance: A total of 158 control oocytes underwent ICSI with a 67.7% survival rate; of these, 65.4% developed to the blastocyst stage. For artificial oocyte activation (AOA), up to 10 oocytes were activated for each experiment, yielding 8 HpBs per activated oocyte. For the experimental group, 556 oocytes underwent enucleation with a 96.4% survival rate. Nuclear transfer of HpBs resulted in a 93.2% survival rate, consistent for those derived from BDF and FVB. Reconstructed oocytes showed appropriate development of a novel pseudo-meoitic spindle at a rate of 63.7% for B6D2F1 HpBs and 75.5% for FVB HpBs, and ICSI yielded a 67.1% and 57.7% survival rate, respectively. The fertilization rate for the reconstructed oocytes was 64%. Control oocytes underwent ICSI with a 67.7% survival rate. When evaluating time-lapse parameters, reconstructed embryos created via blastomere nuclear transfer showed asynchrony compared to controls beginning as early as the stage of pronuclear fading. While the majority of reconstructed embryos arrested at the 4-cell stage, of those that progressed, 11.3% of those using BDF HpBs and 14.6% of those using FVB HpBs developed to the fully expanded blastocyst stage. This corresponds to a total of 23 reconstructed embryos that developed to the morula or blastocyst stage. Limitations, reasons for caution: While we used single-well embryoscope culture for morphokinetic data collection, group culture is superior to single-embryo culture for mice. Thus, developmental rates may be underestimated by this protocol. Implantation and successful pregnancy are also needed to support the clinical utility of this method in generating gametes. Wider implications of the findings: For women with diminished ovarian reserve, oocyte yield and age-related aneuploidy are limitations to achieving genotyped offspring. Nuclear transfer of HpB can generate sibling oocytes while maintaining genetic information. This model represents a promising path for expanding oocyte yield, allowing genetic assessment of sibling oocytes, and enhancing chances of procreation. Trial registration number: none